(3GdEjVGM hGdJcedIs - (3GdMSf Hf CMeO Hf YHO GdZaGQ GdaGQSqj, CHh Ydj,J (B377 (3g` s ((3jMji Hf Ydj Hf eMeO Hf GdMSf s)
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf CeG Ydi CKQ Pdc CWGd Gddg HbGA Gdedc YVO GdOhdI s
(3BNQgG (B:s
(3hPdc Cf GdUGO hGdTjf GSJWGdJG MJi GJUdJG HeNGQL gPg GdMQha gPG BNQ cJGH GdEjVGM s
(3GdEjVGM aj GdfMh hGdJcedI aj GdJUQjas
(3GfXQ GdLRA GdChd ef (B23-26 (3fMhs
(3fSNI fSNJ ef CUd fajS hGdfSNI ebGHdIs
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdfMhs